2010
DOI: 10.2169/internalmedicine.49.3540
|View full text |Cite
|
Sign up to set email alerts
|

Giant Malignant Insulinoma Which Developed from a Non-Functioning Pancreatic Tumor Over a Long Period of Time

Abstract: Insulinomas are the most common hormone-producing pancreatic neuroendocrine tumors (NETs), which are usually benign, solitary and small. We describe herein a patient with a giant insulinoma (>10 cm in diameter) with concomitant thyroid tumor as detected by Somatostatin receptor scintigraphy (SRS). A 50-yearold man presented hypoglycemic symptoms 20 years after the first detection of a pancreatic tumor, which was ameliorated by administration of a somatostatin analogue, octreotide. SRS showed abnormal uptake by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Since 2001, the mitotic activity, Ki-67 index, and grade have been reported for 17 patients with giant insulinomas (Table 2) [57, 12–14, 16–19, 21]. We compared the grade, the rate of metastases and duration of follow-up of 18 cases, including the present case.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Since 2001, the mitotic activity, Ki-67 index, and grade have been reported for 17 patients with giant insulinomas (Table 2) [57, 12–14, 16–19, 21]. We compared the grade, the rate of metastases and duration of follow-up of 18 cases, including the present case.…”
Section: Discussionmentioning
confidence: 98%
“…The severity of hypoglycemia varies from patient to patient and has no direct relationship with tumor burden [10]. Sugiyama et al [7] suggested that giant insulinoma initially diagnosed as non-functioning pNETs may secondarily become functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En la primera, es posible que un insulinoma con pobre producción de insulina crezca muy lentamente durante un largo período de tiempo sin causar síntomas, hasta que alcanzan un gran tamaño capaz de producir suficiente insulina para inducir los ataques de hipoglicemia (12,20) . En la segunda, es posible que haya un cambio fenotípico de un TNEP no funcionante que facilite su transformación a un tumor productor de insulina (21) .…”
Section: Discussionunclassified
“…The natural history of insulinomas suggests that malignant transition from benign disease is rare [17]. Other trigger factors for such transition or de-novo occurrence of insulinomas are currently only speculative and not too well known.…”
Section: Glucocorticoidsmentioning
confidence: 99%